String cavitation formation inside fuel injectors. (November 2015) - Reid, B A; Gavaises, M; Mitroglou, N; Hargrave, G K; Garner, C P; McDavid, R M
Abstract: The formation of vortex or 'string' cavitation has been visualised at pressures up to 2000 bar in an automotive-sized optical diesel fuel injector nozzle. The multi-hole nozzle geometry studied allowed observation of the hole-to-hole vortex interaction and, in particular, that of a bridging vortex in the sac region between the holes. Above a threshold Reynolds number, their formation and appearance during a 2 ms injection event was repeatable and independent of upstream pressure and cavitation number. In addition, two different hole layouts and threedimensional flow simulations have been employed to describe how, the relative positions of adjacent holes influenced the formation and hole-to-hole interaction of the observed string cavitation vortices, with good agreement between the experimental and simulation results being achieved.